Clinical features of mesotherapy-associated non-tuberculous mycobacterial infections: A systematic review. Issue 4 (3rd November 2022) - Singsing, Melissa E.; Duncan, Steven G.; Vachon, M. Jonathan; Goff, Heather W.
Abstract : Background: Cutaneous infections from non-tuberculous mycobacteria (NTM) are a well-documented but poorly characterized adverse event following mesotherapy injections. Objective: This study aims to consolidate the available literature to characterize demographic and clinical features of mesotherapy-associated NTM infections. Methods: Using PRISMA guidelines, a systematic review of PubMed, Scopus, and Embase databases was undertaken for articles reporting cases of NTM skin infections following mesotherapy. Data were analyzed using Microsoft Excel. Results: Of 1966 search results, 30 articles (N = 423 patients) met inclusion criteria. Studies were largely from South America, and patients were mostly women aged 16-55 with NTM infections arising in the abdomen, buttocks, or thighs. Nearly all patients developed multiple, well-localized lesions without systemic symptoms. Effect summary by meta-analysis revealed most infections resolved after antibiotic therapy, though many patients required multiple antibiotic courses and/or agents to resolve infection. Infections often took weeks to resolve and were complicated by post-treatment scarring. Limitations: The main limitation of this study was the heterogeneity and lack of consistency between case reports. Conclusion: Cutaneous NTM infections associated with mesotherapy generally occur in women of childbearing age, arise from injections contaminated by the environment, and are often complicated by scarring/poor cosmesis and prolonged treatment course.